ORGANIZATION AND REALIZATION OF MAIN AND ADDITIONAL PROFESSIONAL EDUCATION PROGRAMS IN THE LOGISTICS FIELD WITH THE HELP OF INNOVATIVE METHODS AND TECHNOLOGIES - Vitaliy V. Borsch; Vasiliy A. Demin; Zoya S. Sazonova (Высшее образование в России)
The analysis of current methods of problem solving in the field of logistics, transportations and supply chain management shows the information and technological features that have been developed considerably over the recent years, and enables to landmark decisions to increase the companies' processes efficiency. Frequently the learning process in logistics doesn't correspond to the innovation principle. This article reviews approaches providing an innovative learning process relevant to business priorities (activities).